THE RELEVANCE OF THE HEALTH CLEANING PROCEDURE FOR HEALTH - Angélica Ferreira Bedone, Junia; Kelly Ribeiro Gonçalves, Celaine; Couto de Araújo, Diana (Health and Society, 2024)
Objective: The purpose of this work is to recognize studies that address the importance of the procedure for cleaning health products, in order to provide a critical observation to practitioners in the corresponding areas. Method: This article was carried out through an integrative bibliographical review. The research materials were: articles from the Google Scholar portal on this theme in the period of 2022. The research is a bibliographical review, which concerns a structured study developed with based on material published in articles on the Google Scholar portal. Results: The cleaning procedure, being reported as a main period in the treatment of PPS, was recognized in 4 studies, as being the indispensable process that makes the products safer to handle and prepares them for disinfection or sterilization. Five articles researched procedural audits, cleaning, and two articles on device and resource properties. Conclusion: With that intention in mind, the panorama elaborated for this study provided an overview of the reasons related to the cleaning procedure that can influence the disinfection and/or sterilization phase and can provide support for institutes interested in performing self-medication cleaning. Assessment of PPS management structures and procedures.